2000
DOI: 10.2139/ssrn.238713
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Fund Survivorship

Abstract: This paper offers a comprehensive study of survivorship issues, in the context of mutual fund research, using the mutual fund data set of Carhart (1997). We find that funds in our sample disappear primarily because of multi-year poor performance. Then we demonstrate analytically that this survival rule typically causes the survivor bias in average performance to increase in the length of the sample period, though it is possible to construct counterexamples. In the data, we find a strong positive relation betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
86
2
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 106 publications
(96 citation statements)
references
References 24 publications
6
86
2
2
Order By: Relevance
“…Carhart (1997) provides a critical appraisal of the Hendricks et al study. In particular he adjusts for momentum effects in the underlying equity market data and potential survivorship bias in the data (something which the subsequent article by Carhart et al 2002 and a number of articles on hedge funds, notably by Malkeil and Saha 2005, explore further). While noting some evidence of superior performance, Carhart's overwhelming conclusion is that "...most funds under-perform by about the magnitude of their investment expenses".…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Carhart (1997) provides a critical appraisal of the Hendricks et al study. In particular he adjusts for momentum effects in the underlying equity market data and potential survivorship bias in the data (something which the subsequent article by Carhart et al 2002 and a number of articles on hedge funds, notably by Malkeil and Saha 2005, explore further). While noting some evidence of superior performance, Carhart's overwhelming conclusion is that "...most funds under-perform by about the magnitude of their investment expenses".…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies of persistence in other asset classes (see, for example Carhart et al 2002) have identified the survivorship bias generated by excluding funds which subsequently "die". This study limits survivorship bias by including some funds which subsequently expire.…”
Section: Fund Numbers Attrition Creation and Biasmentioning
confidence: 99%
“…As the above description shows, the database contains only the surviving funds at the end of the sample period, and therefore suffers from survivorship bias (see Elton et al 2001 andCarhart et al 2002). The effect of this bias on return persistence is addressed in a specific analysis in the last section of the paper.…”
Section: The Databasementioning
confidence: 99%
“…In other words, the only available data are for funds that survive to the end of the sample period. This problem has been addressed in the mutual fund literature, by, among others, Carhart et al (2002) or Brown et al (1992), who show that this type of bias tends to reduce the persistence effect, while Brown et al (1997) reports that survivorship bias may even induce spurious persistence if high-volatility loser funds disappear from the sample. An indirect way of testing whether the return persistence found by this study in the Morningstar database is due to survivorship bias is to check for significant risk differences between the winner and loser portfolios.…”
Section: Survivorship Biasmentioning
confidence: 99%
“…A number of studies such asGrinblatt and Titman (1989),Brown et al (1992),Carpenter and Lynch (1999) andCarhart et al (2002) document the economic significance of survivorship bias in studies of equity mutual fund performance, particularly in relation to the issue of persistence in performance. However, and as noted by DelGuercio and Tkac (2002), studies bySirri and Tufano (1998),Chevalier and Ellison (1997) andGoetzmann and Peles (1997) find that survivorship bias does not affect inferences about the funds flowperformance relationship and, therefore, is not a major issue in studies involving annual tournaments.…”
mentioning
confidence: 99%